The day the earth stood still [videorecording (DVD)] - Wise, Robert, 1914-2005; Rennie, Michael; Neal, Patricia, 1926-2010; Marlowe, Hugh, 1911-1982; Bates, Harry, 1900-1981 (Twentieth Century-Fox Home Entertainment, 2002)
"A spaceship lands in Washington, D.C., capturing the attention of the world. But the alien emissary (Michael Rennie) it brings refuses to reveal his mission to any single government, leaving the military, the politicians, and millions of ordinary people to wait in fear. Soon their distrust turns to calls for violence. But one young woman and her son (Patricia Neal, Billy Gray) befriend him ... and soon realize that they may be all that stands between the human race and total destruction"--Container.